2022
DOI: 10.1101/2022.11.06.22281979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic review of the prevalence of Long Covid

Abstract: Background: Long Covid occurs in those infected with SARSCoV2 whose symptoms persist or develop beyond the acute phase. We conducted a systematic review to determine the prevalence of persistent symptoms, functional disability or pathological changes in adults or children at least 12 weeks post-infection. Methods: We searched MEDLINE (Ovid), Embase (OVID), the Cochrane Covid-19 Study register, WHO ICTRP, medRxiv, Cochrane CENTRAL, MEDLINE (PubMed), ClinicalTrials.gov, and the WHO Global research on coronavirus… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 136 publications
1
3
0
Order By: Relevance
“…Woodrow et al found a prevalence estimate of 42.1% in their systematic review, with values ranging from 0% to 93% in the various studies selected [3]. This result agrees with another meta-analysis estimating a global PCC prevalence of 43% [4], while another paper showed that 80% of individuals with a confirmed COVID-19 diagnosis presented at least one long-term symptom [5].…”
Section: Introductionsupporting
confidence: 65%
“…Woodrow et al found a prevalence estimate of 42.1% in their systematic review, with values ranging from 0% to 93% in the various studies selected [3]. This result agrees with another meta-analysis estimating a global PCC prevalence of 43% [4], while another paper showed that 80% of individuals with a confirmed COVID-19 diagnosis presented at least one long-term symptom [5].…”
Section: Introductionsupporting
confidence: 65%
“…Some findings from this study show similarities with other Long Covid studies. Most notably, the varying range of symptoms experienced, 4–8 the lack of Long Covid awareness among some population groups, 7,47,48 self‐doubt regarding Long Covid as a cause for illness, 7 symptoms as a barrier to accessing care, 47 problems accessing primary care, 6,10,49 experiences of symptoms being dismissed, 10,32,50 seeking support outside the NHS and making behavioural changes, 6,11,49–51 as well as stigma 6,50,51 and discrimination 49 which can all act as barriers to obtaining support and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Long Covid can cause varying symptoms and impact on daily life, including, but not limited to, fatigue, breathlessness, headache, cognitive dysfunction, chest pain, muscle/joint pains, cough, disturbed sleep and neuropsychiatric symptoms 1,4–8 . It can have wide‐ranging negative social impacts that include inhibiting the ability to engage in employment and creating financial burdens 4,9–11 …”
Section: Introductionmentioning
confidence: 99%
“…With the lack of a consensus clinical definition of Long COVID, 20 assessment of the true accuracy of algorithms like ours is challenging. Moreover, the lack of a consistent estimate for Long COVID’s prevalence 21 makes it difficult to determine an appropriate model threshold using real-world evidence. Assessing performance using the U09.9 label as ground truth is the most readily available option, but the inconsistency of the code’s use by providers and its late availability 4 mean that many patients with Long COVID lack the label.…”
Section: Discussionmentioning
confidence: 99%